Predictors of Treatment Success After Periprosthetic Joint Infection: 24-Month Follow up From a Multicenter Prospective Observational Cohort Study of 653 Patients. (2nd February 2022) - Davis, Joshua S; Metcalf, Sarah; Clark, Benjamin; Robinson, J Owen; Huggan, Paul; Luey, Chris; McBride, Stephen; Aboltins, Craig; Nelson, Renjy; Campbell, David; Solomon, L Bogdan; Schneider, Kellie; et al.
Abstract: Background: Periprosthetic joint infection (PJI) is a devastating condition and there is a lack of evidence to guide its management. We hypothesized that treatment success is independently associated with modifiable variables in surgical and antibiotic management. Methods: The is a prospective, observational study at 27 hospitals across Australia and New Zealand. Newly diagnosed large joint PJIs were eligible. Data were collected at baseline and at 3, 12, and 24 months. The main outcome measures at 24 months were clinical cure (defined as all of the following: alive, absence of clinical or microbiological evidence of infection, and not requiring ongoing antibiotic therapy) and treatment success (clinical cure plus index prosthesis still in place). Results: Twenty-four-month outcome data were available for 653 patients. Overall, 449 patients (69%) experienced clinical cure and 350 (54%) had treatment success. The most common treatment strategy was debridement and implant retention (DAIR), with success rates highest in early postimplant infections (119 of 160, 74%) and lower in late acute (132 of 267, 49%) and chronic (63 of 142, 44%) infections. Selected comorbidities, knee joint, and Staphylococcus aureus infections were independently associated with treatment failure, but antibiotic choice and duration (including rifampicin use) and extent of debridement were not. Conclusions: Treatment success in PJI is associated with (1) selecting the appropriate treatment strategy and (2) nonmodifiable patient and infection factors. Interdisciplinary decision making that matches an individual patient to an appropriate management strategy is a critical step for PJI management. Randomized controlled trials are needed to determine the role of rifampicin in patients managed with DAIR and the optimal surgical strategy for late-acute PJI. Abstract : This large observational study of prosthetic joint infection suggests that debridement and implant retention should be reserved for early postimplant infections and that matching a patient to the appropriate management strategy is the key role of treating clinicians.